Gene Expression Profiling of Lymph Node Sub-Capsular Sinus Macrophages in Cancer - Pellin, Danilo; Claudio, Natalie; Guo, Zihan; Ziglari, Tahereh; Pucci, Ferdinando (Frontiers in Immunology, 2021)
Lymph nodes are key lymphoid organs collecting lymph fluid and migratory cells from the tissue area they survey. When cancerous cells arise within a tissue, the sentinel lymph node is the first immunological organ to mount an immune response. Sub-capsular sinus macrophages (SSMs) are specialized macrophages residing in the lymph nodes that play important roles as gatekeepers against particulate antigenic material. In the context of cancer, SSMs capture tumor-derived extracellular vesicles (tEVs), a form of particulate antigen released in high amounts by tumor cells. We and others have recently demonstrated that SSMs possess anti-tumor activity because in their absence tumors progress faster. A comprehensive profiling of SSMs represents an important first step to identify the cellular and molecular mechanisms responsible for SSM anti-tumor activity. Unfortunately, the isolation of SSMs for molecular analyses is very challenging. Here, we combined an optimized dissociation protocol, careful marker selection and stringent gating strategies to highly purify SSMs. We provide evidence of decreased T and B cell contamination, which allowed us to reveal the gene expression profile of this elusive macrophage subset. Squamous cell carcinomas induced an increase in the expression of Fc receptors, lysosomal and proteasomal enzymes in SSMs. Imaging of mouse and patient lymph nodes confirmed the presence of the top differentially expressed genes. These results suggest that SSMs respond to tumor formation by upregulating the machinery necessary for presentation of tumor particulate antigens to B cells.